Concept of company's capital structure - Koliesnichenko, Anastasiia; Bilgen, Selim (Державний біотехнологічнийуніверситет, 2023)
The capital structure appears to be one of the most researched and the most controversial areas in modern corporate finance. Capital structure has been defined by many authors and scholars. However, these definitions require more detailed interpretation and systematization for further analysis and management. Research on theoretical issues regarding the capital structure continues to be relevant, and therefore it is necessary to constantly study this area. Carrying out a systematic review of aspects of the literature regarding the key features and elements of the capital structure allows us to single out such its concept elements as assets, debt, оwn funds, borrowed funds, profitability, financial stability, risk and financial statements.
Keywords: capital structure; profitability; financial stability; risk; management